2017
DOI: 10.1021/acs.jpca.7b02824
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Molecular Dynamics Simulations to Understand Mechanical Response of Thaumasite under Temperature and Strain Rate Effects

Abstract: Understanding the structural, thermal, and mechanical properties of thaumasite is of great interest to the cement industry, mainly because it is the phase responsible for the aging and deterioration of civil infrastructures made of cementitious materials attacked by external sources of sulfate. Despite the importance, effects of temperature and strain rate on the mechanical response of thaumasite had remained unexplored prior to the current study, in which the mechanical properties of thaumasite are fully char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For Si-O, they are 4.06, 4.12 (2 × 1 × 2), and 4.23 for the 1 × 1 × 2, 2 × 1 × 2, and 2 × 2 × 2 systems, respectively, clearly indicating an increase of the Si-O coordination number for larger unit cells, due to the presence of these highly-coordinated motifs. It is worth mentioning that Si atoms with coordination numbers larger than 4 have been reported in a couple of synthesized minerals; namely, a high-pressure phase of MgSi(OH) 6 [126] and a dense phase (so-called phase D) of MgSi(OH) 2 O 4 [127,128], predicted by means of theoretical calculations to occur in thaumasite [129], a naturally-occurring mineral present in the Earth's crust. For Mg-O, the coordination numbers are kept at 5.82 for all unit cell systems, probably due to compensation effects in the different Mg coordination spheres.…”
Section: Unit Cell Size Effects In the Amorphisation Of The Mg 2 Sio mentioning
confidence: 99%
“…For Si-O, they are 4.06, 4.12 (2 × 1 × 2), and 4.23 for the 1 × 1 × 2, 2 × 1 × 2, and 2 × 2 × 2 systems, respectively, clearly indicating an increase of the Si-O coordination number for larger unit cells, due to the presence of these highly-coordinated motifs. It is worth mentioning that Si atoms with coordination numbers larger than 4 have been reported in a couple of synthesized minerals; namely, a high-pressure phase of MgSi(OH) 6 [126] and a dense phase (so-called phase D) of MgSi(OH) 2 O 4 [127,128], predicted by means of theoretical calculations to occur in thaumasite [129], a naturally-occurring mineral present in the Earth's crust. For Mg-O, the coordination numbers are kept at 5.82 for all unit cell systems, probably due to compensation effects in the different Mg coordination spheres.…”
Section: Unit Cell Size Effects In the Amorphisation Of The Mg 2 Sio mentioning
confidence: 99%
“…Furthermore, molecular dynamics (MD) simulation has predicted that the stress‐strain relationships of thaumasite are substantially dependent on the direction of the applied strain. This study also revealed that the mechanical strength of thaumasite differed depending on the orthogonal directions …”
Section: Introductionmentioning
confidence: 59%
“…This study also revealed that the mechanical strength of thaumasite differed depending on the orthogonal directions. 14 The application of cementitious materials under severe conditions requires complete understanding of the mineral characteristics of constituent crystals. Although the temperature-related stability and elastic properties of thaumasite near ambient conditions have been studied, no article has reported the structural changes of thaumasite under high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…A periodic boundary condition is applied to the three spatial directions of each simulation box. The Polak–Ribiere version of the conjugate gradient algorithm is used to minimize the potential energy of the atomistic models. The energy-minimized models are then equilibrated using the MD method in an isothermal–isobaric ensemble (NPT) at 450 K and 0 bar for 1.0 ns (nanosecond, 10 –9 s).…”
Section: Computational Detailsmentioning
confidence: 99%